Development of Android-Based Learning Media on Dynamics and Atmospheric Stability Material - Yayat Ruhiat; Suherman Suherman; Hesti Gustini (Universitas Lambung Mangkurat, 2023)
By employing device technology, or what is known as mobile learning, this project intends to create Android-based goods as learning mediums. A different type of learning medium is mobile learning. The availability of mobile learning can facilitate learning for students by enabling them to acquire difficult content anywhere and at any time. This content was created in a visual and audiovisual style for Android. The ADDIE Development model and research in research and development (R&D) are utilized to accomplish this purpose. This paradigm's five steps are analysis, design, development, implementation, and evaluation. Material expert and material expert tests were performed to evaluate the consistency of the medium and content. A very practical category was produced due to the two experts' determination of the product's validity. Tests on material experts were conducted to ascertain the coherence between the medium and the material. The two experts' product results were valid, and they created a workable category. The media experts' validation results averaged 90.06%, which met the